DISTINCTIVE FEATURES OF TEACHING THE SCIENTIFIC HERITAGE OF JADIDS - Shaturaeva Sevara Tashmuratovna (Scholars Digest Publishing, 2025)
In the second half of the 19th and early 20th centuries, the jadidism movement in Turkestan played an important role in the direction of national identity awareness and enlightenment. During this period, the development of the educational system was of great importance in the cultural and social development of society, and the methods of ancient education began to be replaced by new pedagogical approaches. In such changes of time, the jadids put forward the need for large-scale reforms in education. Their main goal was the development of Science, the expansion of literacy and the cultural growth of society.
Keywords: Jadidism movement, scientists, innovative approach, national culture, society and state.